John Austin or Jane Austen? : the province of jurisprudence determined in Pride and prejudice - W. MacNeil (Law Text Culture, 1998)
It used to be a truth universally acknowledged that the novels of Jane Austen were narratives in want of context. The Napoleonic Wars, industrialisation and the French Revolution: in fact, all the great and heroic events of the period are conspicuous by their absence in the 'little bit (two Inches wide) of ivory' upon which dear Jane worked with 'so Fine a brush'. Post-colonial critics, however, have sensitised readers to the traces of context on the margins of Austen's oeuvre, and how, despite this marginality or perhaps, as the Derrideans would say, because of it - they perform an absolutely central function in terms of the novels's plotting, characterology and thematics. For example, the imperial context of Mansfield Park is the principal focus of Edward Said's celebrated reading of that text in Culture and Imperialism (1994: 95-116).